Method of an enhanced self-amplified spontaneous emission for x-ray free electron lasers - Alexander A. Zholents (Physical Review Special Topics. Accelerators and Beams, 2005)
We describe a technique by which an energy modulation of electrons via interaction with a laser pulse in a wiggler magnet is used for a significant increase of the electron peak current prior to entering a long self-amplified spontaneous emission (SASE) free electron laser undulator. This results in a reduction of the gain length for the SASE process and a modification of the structure of the output x-ray radiation. It also temporally links the output x-ray pulse to the initial laser pulse, thus providing an opportunity for accurate synchronization between the laser pump pulse and x-ray probe pulse for pump-probe experiments.